Calculations of the surface energy of simple liquid metals - Kumaravadivel, R.; Evans, R. (My University, 1975)
Calculations of the surface energy of eleven liquid metals are presented. These are based on the recently proposed pseudo-atom theory of Evans (see abstr. A72625 of 1974). The results are in good agreement with experiment for the alkali metals but overestimate the magnitude of the surface energy for several of the polyvalent metals.